Optimization of the Vibrational Comfort of Passenger Vehicles through Improvement of Suspension and Engine Rubber Mounting Setups - Felipe L. Mrad; Duarte M. L. Machado; Gutierrez J.C. Horta; Almeida U. Sad (Shock and Vibration)
The aim of this work is to develop a measurement methodology to perform a vibration analysis of a vehicle. It proposes new setups in the suspension systems, including springs, shock absorbers, and rubber mountings of the engine system, to improve the passengers’ comfort levels. The influence of each of these modifications in the vibration levels at specific points is analyzed. The importance of human interaction analysis is clear as, in the past, it was frequently left aside. This is because only the vehicle dynamic behavior is generally emphasized in the vehicles designed. Therefore, this work stresses that concerns about human vibration levels result in vehicles with good performance also in comfort levels, focusing on the users’ well-being. A combination of different sets of rubber mountings, springs, and shock absorbers are tested. The changes proposed in this paper are analyzed in sequence and, based on the results, the best combination is proposed.